Über-Alienated: Powerless and Alone in the Gig Economy. Issue 4 (November 2021) - Glavin, Paul; Bierman, Alex; Schieman, Scott
While the gig economy has expanded rapidly in the last decade, few have studied the psychological ramifications of working for an online labor platform. Guided by classical and modern theories of work and alienation, we investigate whether engagement in platform work is associated with an increased sense of powerlessness and isolation. We analyze data from two national surveys of workers from the Canadian Quality of Work and Economic Life Study in September 2019 ( N = 2, 460) and March 2020 ( N = 2, 469). Analyses reveal greater levels of powerlessness and loneliness among platform workers—a pattern that is not fully explained by their higher levels of financial strain. Additional analyses of platform activity reveal that rideshare driving is more strongly associated with powerlessness and isolation than engagement in online crowdwork. We interpret our findings in light of platform firms' use of algorithmic control and distancing strategies that may undermine worker autonomy and social connection.